2020
DOI: 10.1186/s12881-020-0990-9
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase M1 and T1 genes deletion polymorphisms and risk of developing essential hypertension: a case-control study in Burkina Faso population (West Africa)

Abstract: Background: Glutathione S-transferases play a key role in the detoxification of persistent oxidative stress products which are one of several risks factors that may be associated with many types of disease processes such as cancer, diabetes, and hypertension. In the present study, we characterize the null genotypes of GSTM1 and GSTT1 in order to investigate the association between them and the risk of developing essential hypertension. Methods: We conducted a case-control study in Burkina Faso, including 245 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The frequencies of GSTM null and GSTT1 null varies widely in different populations. Previous studies in Burkina Faso reported that approximately 28.75%–31.23% and 30%–55.76% of the population have the null variant of GSTM1 and GSTT1 respectively [ 12 , 38 ], which fell into the range of allele frequency values registered in west African Nigeria (0.3 for GSTM1 null allele; 0.37 for GSTT1 null allele) [ 39 ] and other Black African populations [ 40 ]. GSTM1 and GSTT1 play a key role in the metabolism of certain drugs and xenobiotic through their participation in the second phase of xenobiotic metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies of GSTM null and GSTT1 null varies widely in different populations. Previous studies in Burkina Faso reported that approximately 28.75%–31.23% and 30%–55.76% of the population have the null variant of GSTM1 and GSTT1 respectively [ 12 , 38 ], which fell into the range of allele frequency values registered in west African Nigeria (0.3 for GSTM1 null allele; 0.37 for GSTT1 null allele) [ 39 ] and other Black African populations [ 40 ]. GSTM1 and GSTT1 play a key role in the metabolism of certain drugs and xenobiotic through their participation in the second phase of xenobiotic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no study to our knowledge has evaluated the link between GST gene polymorphisms and response to antihypertensive drugs, although Glutathione S-transferases Mu1 deletion has been associated with resistant hypertension [ 11 ]. We previously investigated the link between Glutathione S-transferases Mu1 ( GSTM1 ) and theta 1 ( GSTT1 ) variants and the risk of developing essential hypertension and found that GSTT1-null genotype was associated with the risk of developing hypertension in Burkina Faso [ 12 ]. In the present study, we want to specifically determine the implication of GSTM1/GSTT1 deletion polymorphisms in BP control among the followed hypertensive patients in the same population.…”
Section: Introductionmentioning
confidence: 99%
“…BP was measured using an electronic cuffed sphygmomanometer by cardiologist as described previously [15].…”
Section: Samples and Data Collectionmentioning
confidence: 99%
“…Genotyping of the GSTM1 and GSTT1 genes has been previously described [15]. Brie y we performed multiplex PCR with the GeneAmp PCR system 9700 (Applied Biosystem, USA) in a reaction volume of 25µL including 10µL of Master Mix AmpliTaq Gold® (Applied Biosystems, USA), 7µL of nuclease-free water, 5µL of DNA and 1µL of each primer pairs for each gene (β-globin, GSTM1, GSTT1).…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation